PENGARUH KARAKTERISTIK KARYAWAN PANEN TERHADAP PRODUKTIVITAS PANEN DI PT. BERAU KARETINDO LESTARI - Dwi Krismantoro; Wartomo; Budi Winarni (Politeknik Pertanian Negeri Samarinda, 2022)
Good management of palm oil harvesters can reduce labor error rate during harvest, increasing work productivity, while also facilitate the achievement of company goals. This research aims to determine the effect of workforce characteristics, namely age, length of work and education on the productivity of palm oil harvest, as well as to determine whether harvest productivity is in accordance with company targets. The results of this research are expected to provide input for companies regarding the productivity of palm oil harvest and also as a reference for recruiting harvesters. Data analysis method used in this research is multiple linear regression. Result is determined using census method, as the sample is less than 100 people with the number of respondents reached 52 people. Based on the research results, it was indicated that length of work, age and education do not affect the productivity of harvesters at Long Ayan Estate PT. Berau Karetindo Lestari. The average labor productivity of harvesters reached 281.06 bunches/weekdays; thus, the workforce was able to achieve the target set by the company of 175 bunches/weekdays.